22-gauge core vs 22-gauge aspiration needle for endoscopic ultrasound-guided sampling of abdominal masses - Sterlacci, William; Sioulas, Athanasios D.; Veits, Lothar; Gönüllü, Pervin; Schachschal, Guido; Groth, Stefan; Anders, Mario; Kontos, Christos K.; Topalidis, Theodoros; Hinsch, Andrea; Vieth, Michael; Rösch, Thomas; et al. (World Journal of Gastroenterology, 2016)
AIM To compare the aspiration needle (AN) and core biopsy needle (PC) in endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) of abdominal masses. METHODS Consecutive patients referred for EUS-FNA were included in this prospective single-center trial. Each patient underwent a puncture of the lesion with both standard 22-gauge (G) AN (Echo Tip Ultra; Cook Medical, Bloomington, Indiana, United States) and the novel 22G PC (EchoTip ProCore; Cook Medical, Bloomington, Indiana, United States) in a randomized fashion; histology was attempted in the PC group only. The main study endpoint was the overall diagnostic accuracy, including the contribution of histology to the final diagnosis. Secondary outcome measures included material adequacy, number of needle passes, and complications. RESULTS Fifty six consecutive patients (29 men; mean age 68 years) with pancreatic lesions (n = 38), lymphadenopathy (n = 13), submucosal tumors (n = 4), or others lesions (n = 1) underwent EUS-FNA using both of the needles in a randomized order. AN and PC reached similar overall results for diagnostic accuracy (AN: 88.9 vs PC: 96.1, P = 0.25), specimen adequacy (AN: 96.4% vs PC: 91.1%, P = 0.38), mean number of passes (AN: 1.5 vs PC: 1.7, P = 0.14), mean cellularity score (AN: 1.7 vs PC: 1.1, P = 0.058), and complications (none). A diagnosis on the basis of histology was achieved in the PC group in 36 (64.3%) patients, and in 2 of those as the sole modality. In patients with available histology the mean cellularity score was higher for AN (AN: 1.7 vs PC: 1.0, P = 0.034); no other differences were of statistical significance. CONCLUSION Both needles achieved high overall diagnostic yields and similar performance characteristics for cytological diagnosis; histological analysis was only possible in 2/3 of cases with the new needle.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Abdominal tumors; Core biopsy needle; Cytology; Endoscopic ultrasound; Fine needle aspiration